Belonging and Global Citizenship in a STEM University - Julianne K. Viola (MDPI AG, 2021)
For the past two decades, there has been a resurgence in the actualization of civic missions in universities; these universities have continued to demonstrate commitment to educate for the purpose of global citizenship. Global citizenship is both a skillset and a mindset. As universities engage in efforts to increase students' capabilities for living and working in a diverse society, research in this area has often focused on students of social science disciplines in the United States, presenting an opportunity for an investigation into students' sense of belonging and global citizenship in the STEM university context in the United Kingdom. Building on prior civic scholarship, which defines citizenship in part as a sense of belonging, this paper presents interview data from a longitudinal, mixed-methods study at a STEM university in the United Kingdom to explore the meanings and experiences of students' belonging in a multicultural institution, and their attitudes about current political issues before and during the COVID-19 pandemic. The study presents theoretical and practical implications for citizenship education research and practice.